2006
DOI: 10.1007/s10157-006-0439-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an educational program on the predialysis period for patients with chronic renal failure

Abstract: This study suggests that providing sufficient information before dialysis initiation may be effective in both physical condition at dialysis initiation, and medical economic benefits through the understanding of the dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 13 publications
0
24
1
4
Order By: Relevance
“…These authors found that the number of patients using a double-lumen dialysis catheter, and the duration and cost of hospitalization in training the participating group, were significantly less than those in the nonparticipating group. Also although there was no significant difference in renal function at the initiation of renal replacement therapy between the two groups-serum albumin, hemoglobin, and hematocrit in the participating group were significantly higher than in the nonparticipating group [91]. Roderick et al reported that for patients whose referral to a nephrologist was delayed, laboratory results were significantly worse at the start of RRT, they were less likely to have received standard treatments for CKD, fewer of them had a permanent dialysis access in place at the start of RRT (18 vs. 47%, P = 0.001), and they had a significantly longer initial stay in hospital (18 vs. 10 days, P = 0.001) [95,96].…”
Section: Role Of Predialysis Trainingmentioning
confidence: 61%
See 2 more Smart Citations
“…These authors found that the number of patients using a double-lumen dialysis catheter, and the duration and cost of hospitalization in training the participating group, were significantly less than those in the nonparticipating group. Also although there was no significant difference in renal function at the initiation of renal replacement therapy between the two groups-serum albumin, hemoglobin, and hematocrit in the participating group were significantly higher than in the nonparticipating group [91]. Roderick et al reported that for patients whose referral to a nephrologist was delayed, laboratory results were significantly worse at the start of RRT, they were less likely to have received standard treatments for CKD, fewer of them had a permanent dialysis access in place at the start of RRT (18 vs. 47%, P = 0.001), and they had a significantly longer initial stay in hospital (18 vs. 10 days, P = 0.001) [95,96].…”
Section: Role Of Predialysis Trainingmentioning
confidence: 61%
“…All now recognize the benefits of medical management in the predialysis period (i.e., the period before dialysis initiation) including the use of renin angiotensin inhibitors, strict control of blood pressure, a reduction in anemia, dietary therapy, and control of calcium and phosphate levels. Reports now indicate that implementation of these measures in the predialysis period, especially in CKD stages 2-4, retard deterioration or even improve renal function, prevent the progression or development of complications, and defer the need for renal replacement [91]. A recent paper examined the initial characteristics of patients referred in various stages of CKD and tried to identify factors associated with subsequent changes in estimated glomerular filtration rate (eGFR).…”
Section: Role Of Predialysis Trainingmentioning
confidence: 98%
See 1 more Smart Citation
“…We therefore consider the criteria adopted for ER to be valid. It has been reported that patient education by specialist staff headed by nephrologists prior to the initiation of HD decreases the likelihood of the need for urgent dialysis, resulting in a decrease in the need for the creation of a temporary VA [13]. Lee et al [14] reported that a permanent VA had been created beforehand in 46.5% of the patients followed up by a nephrologist.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that patient education by nephrologists before initiation of dialysis decreases the likelihood of the need for urgent dialysis, resulting in a reduction in the need for the creation of a temporary vascular access [27]. Schmidt et al showed that the need for emergency HD was significantly less among ER patients compared with LR patients (22% versus 90%) [13].…”
Section: Discussionmentioning
confidence: 99%